Assisting Pregnant Women in Reducing Anxiety and Lower Back Painwith Progressive Muscle Relaxation - Anuhgera, Diah Evawanna; Damayanti, Damayanti; Ritonga, Nikmah Jalilah (JURNAL PENGMAS KESTRA (JPK), 2025)
Anxiety in pregnancy often occurs due to psychological changes and physical changes that cause discomfort, causing the mother to become anxious. One of the physical changes that occurs rapidly during pregnancy is the increasing gestational age, causing the pregnant woman to experience physiological lordosis to lower back pain. Assistance during pregnancy by introducing, demonstrating and monitoring the process of implementing progressive muscle relaxation will make pregnant women more confident in overcoming anxiety and lower back pain during pregnancy so that the mother is able to empower herself during pregnancy. The purpose of this service is to provide assistance to pregnant women with progressive muscle relaxation actions in reducing anxiety and lower back pain during pregnancy. This activity is carried out using the lecture method, question and answer, demonstration, and activity evaluation. The assistance activity was carried out 4 times. The implementation procedure includes socialization, training, lectures, question and answer, demonstration, and activity evaluation. The results of the assistance activity increased knowledge from 16.6% to 75% after assistance. The skills of pregnant women also increased in practicing progressive muscle relaxation by 66.66% after assistance. Assistance efforts can be carried out with a longer duration of time and with innovative method updates such as the use of digital media. This activity is effective to be implemented for pregnant women as a form of self-empowerment during pregnancy.. should be minimum.